A walk through the landscape of writing: Insights from a program of writing research. Issue 2 (3rd April 2022) - Graham, Steve
Abstract: This article is an expanded version of my presentation to Division 15 (Educational Psychology) of the American Psychological Association for the Career Achievement Award for Distinguished Psychological Contributions to Education in 2019. It provides an overview of research conducted by colleagues and I that examined the following four topics: (a) the role of writing knowledge, strategies, motivation, and skills in writing and students' growth as writers; (b) the connections between writing, language, reading, and learning; (c) the identification of effective writing practices; and (d) the current state of writing instruction in schools. For each topic, I provide examples of the logic and the different types of evidence collected in studying each area. Concluding comments focus on areas still in need of investigation.